2005
DOI: 10.1126/science.1115193
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Changes to the Global Methane Budget over the Past 2000 Years

Abstract: We report a 2000-year Antarctic ice-core record of stable carbon isotope measurements in atmospheric methane (delta13CH4). Large delta13CH4 variations indicate that the methane budget varied unexpectedly during the late preindustrial Holocene (circa 0 to 1700 A.D.). During the first thousand years (0 to 1000 A.D.), delta13CH4 was at least 2 per mil enriched compared to expected values, and during the following 700 years, an about 2 per mil depletion occurred. Our modeled methane source partitioning implies tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
365
3
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 338 publications
(410 citation statements)
references
References 26 publications
38
365
3
4
Order By: Relevance
“…This period of low CO 2 coincides with high ı 13 C interpreted by the KFDD as terrestrial uptake, which could be caused by a decrease of the Northern Hemispheric or global surface temperature [Mann et al, 2008;Oppo et al, 2009] Trudinger et al [1999] suggested that the lower temperature reduced both the release of CO 2 (soil respiration) and the uptake (photosynthesis) of CO 2 by the terrestrial biosphere, with the respiration reduction dominating, causing the terrestrial biosphere to accumulate carbon. Lower atmospheric CH 4 was found to be a likely result of land surface cooling during that period [Etheridge et al, 1998;Ferretti et al, 2006;Mitchell et al, 2011].…”
Section: Preindustrialmentioning
confidence: 99%
“…This period of low CO 2 coincides with high ı 13 C interpreted by the KFDD as terrestrial uptake, which could be caused by a decrease of the Northern Hemispheric or global surface temperature [Mann et al, 2008;Oppo et al, 2009] Trudinger et al [1999] suggested that the lower temperature reduced both the release of CO 2 (soil respiration) and the uptake (photosynthesis) of CO 2 by the terrestrial biosphere, with the respiration reduction dominating, causing the terrestrial biosphere to accumulate carbon. Lower atmospheric CH 4 was found to be a likely result of land surface cooling during that period [Etheridge et al, 1998;Ferretti et al, 2006;Mitchell et al, 2011].…”
Section: Preindustrialmentioning
confidence: 99%
“…For all measured parameters, we chose to state the uncertainty with the highest value, independent of the method from which it was derived. We therefore conclude a measurement uncertainty of 0.09 ‰ for δ 13 C-CH 4 (BFI), 0.6 ‰ for δ 15 N-N 2 O (QCS) and 0.7 ‰ for δ 18 O-N 2 O (BFI), which is comparable to or better than those of Sowers et al (2003), Ferretti et al (2005), Schaefer and Whiticar (2007), Behrens et al (2008), Sowers (2009), Sapart et al (2011) and Melton et al (2011b).…”
Section: Precision Of the Setupmentioning
confidence: 86%
“…Brenninkmeijer et al (2003) describe how the isotope fractionation of specific source and sink processes affect the integrated isotopic composition of the respective trace gases in the atmosphere. In an inverse approach, ice core isotope records of CH 4 and N 2 O provide distinct constraints on biogeochemical processes that can be linked to the variability observed in the CH 4 and N 2 O mixing ratios on decadal to millennial timescales (Sowers et al, 2003(Sowers et al, , 2005Sowers, 2006Sowers, , 2009Ferretti et al, 2005;Schaefer et al, 2006;Bock et al, 2010b;Melton et al, 2011a;Sapart et al, 2012). Because ice core records of CH 4 and N 2 O isotopic composition indicate the natural response of specific greenhouse gas sinks and sources to palaeoclimate changes, this information is of great interest to global warming predictions.…”
Section: P Sperlich Et Al: Ch 4 and N 2 O Isotopes In Ice Core Samplesmentioning
confidence: 99%
“…Etheridge et al 1998) as well as firn air and ice cores (Ferretti et al 2005;Sowers et al 2005) show methane became isotopically heavier during the twentieth century (values increasing from K49‰ to just above K47‰). This implies a shift in the balance of sources towards those that are isotopically heavy (fossil and pyrogenic) in comparison with the isotopically light biogenic sources.…”
Section: The Last 2000 Yearsmentioning
confidence: 99%